Implementasi Kode Etik Guru Terhadap Proses Pembelajaran - Rusman, Abdul Hamid; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the implementation of teachers’ code of ethics in the learning process, and to explore in depth the concepts, principles, challenges, and practical solutions to the application of professional ethics in the era of globalization and digital transformation. As the central component of the education system, teachers play a vital role in shaping students’ character, knowledge, and skills. In carrying out their duties, teachers are expected not only to possess professional, pedagogical, social, and personal competencies, but also to uphold moral values through the consistent application of professional ethical standards. This study employs a descriptive qualitative methodology, utilizing data collection techniques such as literature review, observation, in-depth interviews, and documentation. Data were analyzed qualitatively through the stages of data reduction, data display, and thematic conclusion drawing. To ensure the validity of findings, triangulation of sources, techniques, and time was applied, involving the perspectives of teachers, students, and school principals as key informants. The findings indicate that the majority of teachers highly uphold professional ethics in their daily practices—both in their interactions with students and in maintaining the image and dignity of the teaching profession within the school and broader community. Nonetheless, the implementation of the code of ethics still faces various challenges, including the weak internalization of ethical values during pre-service education, the lack of regular training and supervision on ethics, and the negative impact of social media on the professional image of teachers. However, when consistently applied, the code of ethics has a significantly positive impact on enhancing teacher professionalism, student learning comfort, and the creation of an ethical, conducive, and dignified learning climate. Therefore, strengthening the code of ethics must be pursued through continuous training, systematic professional character education, and synergistic collaboration among educational institutions, professional organizations, and government bodies